Overview: the prospect of the use of energy crops for biological reclamation of disturbed lands - Shkvirko, Oksana; Tymchuk, Ivan; Holets, Natalia; Malovanyy, Myroslav (Lviv Politechnic Publishing House, 2019)
The article deals with the theoretical principles of the biological reclamation of disturbed lands. The best types of plants to be used for biological reclamation of disturbed lands are determined. The successful experience of biological land reclamation in Ukraine as a result of mining and extraction works is analyzed. The possibility of application of such energy crops as miskanthus, switchgrass, poplar, willow and paulownia
Keywords: recultivation; phytoremediation; disturbed lands; energy crops; miskanthus; switchgrass; poplar; willow; paulownia